2005
DOI: 10.1385/ep:16:3:201
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin CK 7 and CK 20 Expression in Pituitary Adenomas

Abstract: The pattern of immunohistochemical expression of cytokeratins 7 (CK 7) and 20 (CK 20) is commonly used to assess possible primary sites of metastatic carcinomas. Because pituitary tumors are almost always benign, there has been little interest in their cytokeratin profile. However, we recently reported the use of CK 7/20 expression to document malignant progression and metastasis of a pituitary tumor, indicating the potential diagnostic usefulness of the CK 7/20 profile of pituitary adenomas. We analyzed CK 7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
3
15
1
Order By: Relevance
“…Although immunoreactivity for cytokeratin filaments has been documented in Crooke's cells [3][4][5][6][7][8] and positivity for CK8 and CK18 has been reported [7,9], these cytokeratin subsets are not specific for Crooke's cells because many in diagnostic pathology, primarily in ascertaining the primary origin of many types of metastatic adenocarcinomas. In 1992, Moll et al [10] reported that the cells of the pituitary gland were negative for CK20 expression, an observation confirmed in our recent study [13]. However, we also noted that Crooke's cells in a nonneoplastic pituitary gland adjacent to an ACTH adenoma were CK20 positive.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although immunoreactivity for cytokeratin filaments has been documented in Crooke's cells [3][4][5][6][7][8] and positivity for CK8 and CK18 has been reported [7,9], these cytokeratin subsets are not specific for Crooke's cells because many in diagnostic pathology, primarily in ascertaining the primary origin of many types of metastatic adenocarcinomas. In 1992, Moll et al [10] reported that the cells of the pituitary gland were negative for CK20 expression, an observation confirmed in our recent study [13]. However, we also noted that Crooke's cells in a nonneoplastic pituitary gland adjacent to an ACTH adenoma were CK20 positive.…”
Section: Discussionsupporting
confidence: 89%
“…This polypeptide was first described by Moll et al [10], who reported in 1992 that a normal pituitary gland does not express this cytokeratin subtype. We also observed that CK20 immunopositivity is not seen in normal endocrine cells of the anterior pituitary gland, but we noted that Crooke's cells in a nonneoplastic pituitary gland adjacent to an ACTH adenoma were immunopositive for CK20 [13].…”
Section: Introductionmentioning
confidence: 55%
“…Cytokeratin 20 is also always negative in pituitary adenomas. But rare pituitary adenomas like corticotrophs and sparsely granulated growth hormone-positive adenomas are consistently cytokeratin 20 positive and cytokeratin 7 negative [14]. In our patient, the tumor cells were strongly positive for thyroid transcription factor-1 and cytokeratin 7, but negative for cytokeratin 20; growth hormone level was within normal limits.…”
Section: Discussionmentioning
confidence: 40%
“…However, cytokeratin 20 is negative in primary lung adenocarcinomas and positive in colon adenocarcinomas. In pituitary adenomas, the pattern of immunohistochemical expression of cytokeratin 7 and 20 was indicative of the primary tumor origin in lung adenocarcinoma [14]. In about 90% of pituitary adenomas, cytokeratin 7 is either negative or reactive in only a few scattered cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by accumulation of a homogenous, glassy or hyaline substance in the cytoplasm; the hyaline material is composed of keratin filaments and stains with antibodies to low-molecular-weight cytokeratins and more specifically with cytokeratin (CK) 20 [15]. This change results from exposure to glucocorticosteroid excess either by exogenous administration or as a result of endogenous glucocorticoid hypersecretion caused by primary adrenal disease or ectopic ACTH production [5].…”
Section: Crooke's Hyaline Change In Pituitary Adenomasmentioning
confidence: 99%